Attitudes towards people with physical or intellectual disabilities among nursing, social work and medical students. Issue 23 (13th October 2017) - Kritsotakis, George; Galanis, Petros; Papastefanakis, Emmanouil; Meidani, Flora; Philalithis, Anastas E.; Kalokairinou, Athena; Sourtzi, Panayota
Abstract : Aims and objectives: To examine and compare undergraduate healthcare students' attitudes towards people with physical or intellectual disabilities in Greece. Background: The experience that people with disabilities have with health care is a complex interaction between their medical condition and the social and physical environment. Attitudes of the nursing and healthcare staff affect the quality of care and people's adaptation to their disability, self‐image and rehabilitation outcomes. Design: Descriptive cross‐sectional survey. Methods: Nursing, Social Work and Medicine students ( N  = 1007, 79.4% female) attending three universities (Athens, Crete) completed during 2014–2016 two standardised scales regarding physical (ATDP‐B) and intellectual disability (CLAS‐ID). Descriptive and multivariate logistic regression analyses were performed. Results: Attitudes towards people with physical disabilities in Greece (ATDP‐B scores) were poor with scores just above the mid‐point. Medical studies and higher knowledge and work with individuals with physical disabilities signified marginally more positive attitudes. Gender and age displayed no associations with attitudes. Regarding intellectual disability (CLAS‐ID scores), nursing students had slightly less positive attitudes in "Similarity" but more positive attitudes in "Sheltering" subscales. Previous work and contact was related to more favourable and higher age to less favourable "Similarity" and "Sheltering" attitudes. Males had higher "Exclusion" scores. Those who knew people with intellectual disabilities had less favourable "Empowerment" attitudes. Knowledge was related to more positive attitudes in all four CLAS‐ID subscales. Conclusions: Greek health and social care students showed poor attitudes towards people with physical and intellectual disability. Relevance to clinical practice: When holding unfavourable attitudes, healthcare professionals become less involved with the people they care for and they do not provide nursing care to the best of their abilities. Undergraduate and continuing education, along with workplace enhancements, should aim to provide high‐quality health care to people with disabilities.